The Use of Naturally Occurring Cancer in Domestic Animals for Research into Human Cancer: General Considerations and a Review of Canine Skeletal Osteosarcoma - Brodey, Robert S. (1979)
For many years, research into human cancer has concentrated on human patients and on artificially induced neoplasms in inbred murine hosts. Cancer, however, affects a great variety of mammals, particularly those that have been domesticated. Suchf naturally occurring neoplasms are common in dogs, cats, cattle, horses, etc., and offer fertile ground for studies relating to epidemiologyf, etiology, immunobiology, and therapy. Canine osteosarcoma is described in detail. The clinicopathologic features of this canine tumor closely approximate that of human osteosarcoma and thus make canine osteosarcoma an invaluable comparative model. Canine osteosarcoma and other naturally occurring tumors lie intermediate between the mouse models and human cancer. The use of these veterinary models in the future fabric of cancer research will broaden its base and will influence our conceptual approach to research and clinical options.